The Satyricon $1 (BVolume 04 : Escape by Seas - Petronius Arbiter, 20-66; Firebaugh, W. C. (Salt Lake City, UT : Project Gutenberg, 2004)
"The Satyricon $1 (BVolume 04 : Escape by Sea" by Petronius Arbiter is a Latin work of fiction written in the late 1st century AD. This volume continues the bizarre adventures of Encolpius and his companions as they navigate a world of decadence and danger. Mixing prose and verse, the narrative blends serious and comic elements with satirical observations of Roman society. The story follows their chaotic encounters with colorful characters, from wealthy vulgarians to lecherous poets, as they flee complications and pursue survival in the early Roman Empire. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Satyricon
Release date is 2004-06-01
Produced by David Widger
Keywords: Rome -- Fiction; Satire, Latin -- Translations into English